ERRATUM - K. G. Wiryawan (Tropical Animal Science Journal, 2019)
ERRATUM TO: N. Nurhidayah, F. Satrija, & E.B. Retnani. 2019. Gastrointestinal Parasitic Infection of Swamp Buffalo in Banten Province, Indonesia: Prevalence, Risk Factor, and Its Impact on Production Performance. Tropical Animal Science Journal 41(1):6-12 (DOI: https://doi.org/10.5398/tasj.2019.42.1.6)In the version of this published article, the volume written on page 6, that was Tropical Animal Science Journal 41(1):6-12, was incorrect. The correct version is Tropical Animal Science Journal 42(1):6-12. The error has been corrected on the website and PDF versions of the article.